Reproduktion von Georgina Beiers Ölgemälde „Sunbirds“ von 1965 (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 1965)
Copyright exclusively held by Georgina Beier Estate Executor, or jointly by Iwalewahaus, CBCIU. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Art; Women artists; Artists; Painting; Oil Painting